2010
DOI: 10.48550/arxiv.1009.5229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the ridge-like structures in the nuclear and hadronic reactions

Abstract: We briefly comment on the ridge-like structure origin in the nuclear and hadronic reactions emphasizing that this structure in the two-particle correlation function can result from the rotation of the transient state of matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…At such high energies (LHC) the presence of reflective scattering mode serves as a trigger for the mainly peripheral nature of the inelastic interactions and the presence of large orbital angular momenta. Since correlations are maximal in the rotation plane, a narrow ridge should be observed in the two-particle correlation function [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At such high energies (LHC) the presence of reflective scattering mode serves as a trigger for the mainly peripheral nature of the inelastic interactions and the presence of large orbital angular momenta. Since correlations are maximal in the rotation plane, a narrow ridge should be observed in the two-particle correlation function [3].…”
Section: Discussionmentioning
confidence: 99%
“…In this note we discuss the elliptic flow in proton collisions on the base of approach [2] which was applied for discussion of the directed flow and the ridge in proton collisions [3]. This particular approach is based on the non-perturbative hadron dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of long-range correlations in nuclear collisions at RHIC [24] and (very recently) in pp-collisions at the LHC [1] has been studied within the color-glass-condensate approach in [6,7] (see also the more recent papers [8,9]). In our study we refrain from making any assumptions about the structure of the quark-gluon (QG) matter just-before/during/just-after the proton-proton collisions, and appeal instead to a field theoretic description of the particle tracks in terms of path-dependent exponentials along the lines exposed above.…”
Section: Cms Ridge-theoretical Considerationsmentioning
confidence: 99%
“…Theoretical attempts to dig out the physical origin of the ridge structure in the highmultiplicity pp data observed by CMS mainly concentrate on the properties of a particular state of matter-the Color Glass Condensate (CGC)-that was created during the high-energy collision (see, for instance, Refs. [7][8][9]). Other authors claim that the observed ridge may be the manifestation of an azimuthal quadrupole [11], or the result of reflective scattering effects in multiparticle production processes [10].…”
Section: Introductionmentioning
confidence: 99%
“…(14) Neutral particles have to be also taken into account. In view to estimate the total multiplicity we multiply expression ( 14) by 3 2 (isotopic spin of a gluon is zero). Then we estimate √ s = 2∆EM p + M 2 p and corresponding mean multiplicity u :…”
mentioning
confidence: 99%